2014
DOI: 10.1111/ajag.12156
|View full text |Cite
|
Sign up to set email alerts
|

Development of self‐efficacy of newly graduated registered nurses in an aged care program

Abstract: The improved confidence resulting from increased self-efficacy and new knowledge gained from the aged care program enabled nurses to critically appraise the practices in their workplace, demonstrating the program's effectiveness. Aged care service providers should support continuing education for aged care nurses to ensure sustainability of a competent workforce to manage the increasing aged care population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
(14 reference statements)
3
18
0
2
Order By: Relevance
“…More specifically, early career registered nurses with higher levels of general self-efficacy tended to exhibit greater levels of nurse resilience. These findings are consistent with previous research (Lau et al, 2015;Taylor & Reyes, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…More specifically, early career registered nurses with higher levels of general self-efficacy tended to exhibit greater levels of nurse resilience. These findings are consistent with previous research (Lau et al, 2015;Taylor & Reyes, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Nordmark et al (2016) also discovered notably positive correlations between volunteers' organizational commitment and experiential education. Lau et al (2015) indicated that the dimensions in experiential education showed significantly positive correlations with volunteers' "value commitment" and "effort commitment". Besides, experiential education appeared remarkable predictive power on organizational commitment.…”
Section: Research On the Correlation Between Self-efficacy And Organimentioning
confidence: 99%
“…Referring to Lau et al (2015), organizational commitment in this study is divided into (1) value commitment, (2) effort commitment, and (3) retention commitment.…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Özyeterlilik kavramı sosyal bilişsel kurama dayanır ve bireylerin olası bir durumu yönetmek için gerekli olan belirli davranışları organize edip uygulayabilmeleridir. Yani kişinin belirli bir görevde başarılı olma yeteneğine olan inancını ifade etmektedir (Lau, Willetts, Hood, ve Cross, 2015). Özyeterlilik, bireyin belirli eylemleri gerçekleştirme kabiliyetine ilişkin algılarını ifade etmektedir (Bandura, 1978).…”
Section: öZyeterlilikunclassified
“…Özyeterliliği yüksek bireyler, kişisel hedefler belirleyerek bu hedeflere ulaşmak için zor durumların üstesinden gelmede başarılı olacağına inanırlar. Bundan dolayı özyeterlilik öğrenmeyi ve performansı olumlu etkilemektedir (Lau, Willetts, Hood ve Cross, 2015). Yüksek öz-yeterliliğe sahip olan çalışanlar görevlerini başarılı bir şekilde yerine getirecektir.…”
Section: öZyeterlilikunclassified